PERANCANGAN PROTOTYPE SISTEM KEAMANAN PARKIR BERBASIS KARTU MAGNETIC STRIPE - Dodi Afriansyah (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstractKalirejo 1 Central Lampung High School is one of the National Standard Schools with accreditation A. There are hundreds of students who attend school there and most of them ride motorbikes to get to school. For this reason, a parking system is needed that can guarantee the safety of the vehicle. The problem faced by Kalirejo High School 1 is prone to vehicle theft, this is due to the absence of evidence of vehicle parking. For this reason, the authors built an application that can help the school to minimize or even eliminate vehicle theft, especially two-wheeled vehicles. The design of this system aims to overcome the problems that exist in Kalirejo State High School 1 and provide information on the number of vehicles parked each day and reports on the number of vehicles registered.